2022
DOI: 10.5194/cp-2021-172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mid-Holocene rainfall changes in the southwestern Pacific

Abstract: Abstract. A better understanding of ENSO dynamics is essential for modelling future climate change and its impacts on the ecosystems and lives of the inhabitants of the tropical Pacific islands, which face considerable environmental risk in the coming decades. This study reconstructs past ENSO dynamics using a multi-proxy approach applied to a stalagmite from Niue Island that covers the period 6.4–5.4 ka BP. δ18O and δ13C, trace-element concentrations and image analysis are linked to an age-depth model constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
2
1
0
Order By: Relevance
“…While the latter is not significantly affected by the correction, the former can only be identified as less predictable when the variations in sampling rate are taken into account. This result corroborates previous findings that suggested that both of these identified periods were more irregular, i.e., showing less steady seasonal fluctuations [63]. However, it was not possible to characterize all subannual values as a proxy for subannual rainfall distribution rather extracting only the contrast between wet and dry season.…”
Section: Real-world Application: Rainfall Seasonality In the Central ...supporting
confidence: 89%
See 1 more Smart Citation
“…While the latter is not significantly affected by the correction, the former can only be identified as less predictable when the variations in sampling rate are taken into account. This result corroborates previous findings that suggested that both of these identified periods were more irregular, i.e., showing less steady seasonal fluctuations [63]. However, it was not possible to characterize all subannual values as a proxy for subannual rainfall distribution rather extracting only the contrast between wet and dry season.…”
Section: Real-world Application: Rainfall Seasonality In the Central ...supporting
confidence: 89%
“…In particular, an enhanced control of the seasonal cycle by variability was found in [63] for the periods of reduced predictability (6.4 and 6.2 ka BP, and between 5.9 and 5.72 ka BP). High tropical cyclone activity between 6.4-6.2 ka BP could have been triggered by increased El Niño-Southern Oscillation (ENSO) activity, yielding a more irregular subannual distribution of rainfall.…”
Section: Real-world Application: Rainfall Seasonality In the Central ...mentioning
confidence: 93%
“…In the western Pacific, speleothem from Borneo reveal reduction in interannual variability during the mid-Holocene, thus indicating a minimum in ENSO variance (Chen et al, 2016). This observation is supported by findings from western Pacific coral samples (McGregor et al, 2004) and stalagmite from Niue Island (Nava-Fernandez et al, 2022). From about 3.0 to 4.0 ka, increased precipitation in Borneo and cooling of SST in Papua New Guinea also suggests the influence of ENSO in the centre of IPWP .…”
Section: El Niño Southern Oscillation (Enso)supporting
confidence: 59%